The bone conduction implant – a review and 1-year follow-up. (2nd December 2019) - Håkansson, Bo; Reinfeldt, Sabine; Persson, Ann-Charlotte; Jansson, Karl-Johan Fredén; Rigato, Cristina; Hultcrantz, Malou; Eeg-Olofsson, Måns
Abstract: Objective: The objective of this study is to evaluate its safety and effectiveness of the bone conduction implant (BCI) having an implanted transducer and to review similar bone conduction devices. Design: This is a consecutive prospective case series study where the patients were evaluated after 1, 3, 6 and 12 months. Outcome measures were focussed on intraoperative and postoperative safety, the effectiveness of the device in terms of audiological performance and patient's experience. Study sample: Sixteen patients with average age of 40.2 (range 18–74) years have been included. Thirteen patients were operated in Gothenburg and three in Stockholm. Results: It was found that the procedure for installing the BCI is safe and the transmission condition was stable over the follow-up time. No serious adverse events or severe adverse device effects occurred. The hearing sensitivity, speech in noise and the self-assessment as compared with the unaided condition improved significantly with the BCI. These patients also performed similar or better than with a conventional bone conduction reference device on a softband. Conclusions: In summary, it was found that the BCI can provide a safe and effective hearing rehabilitation alternative for patients with mild-to-moderate conductive or mixed hearing impairments.